Application of somatic hybridization for the improvement of horticultural crops - Singh, A.K.; Mishra, N.K.; Kumar, Sanjeev; Pandey, Sudhakar (Horticultural Biotechnology Research, 2015)
Somatic hybridization (SH) using protoplast fusion is a promising tool to produce symmetrical and asymmetrical polyploidy somatic hybrids in many agricultural crops. The technique of SH could facilitate conventional breeding by providing of novel lines so as to use them as elite breeding materials in conventional crosses for both scion and rootstock improvement. Further, SH can overcome those problems associated with sexual hybridization viz., sexual incompatibility, nucellar embryogenesis, and male/female sterility. Successful exploitation of SH in horticultural crops mainly comes from transfer of resistance genes for biotic and abiotic stresses from related species in several horticultural crops, viz., citrus, potato, brinjal, tomato, mango, avocado, banana, strawberry, pear, cherry etc. Unlike transgenic technology, SH is not affected by legal formalities and able to transfer uncloned multiple genes. However, certain boundaries and limitations of SH restricts its use over sexual hybridization but, envisage of new genomic technologies providing better insight into the plant genomes will increase the potentiality of SH in betterment of agriculture.